2017
DOI: 10.1590/0004-282x20170069
|View full text |Cite
|
Sign up to set email alerts
|

ID-Migraine™ questionnaire and accurate diagnosis of migraine

Abstract: Headache is a major worldwide health problem and the second most common type is migraine, with a global prevalence among adults greater than 10%. Migraine mainly affects adults between 25 and 55 years, during the most productive years of life 1 . In Brazil, the prevalence of migraine is estimated to be 15.2% 2 .Lipton et al. 3 demonstrated that migraine is still underdiagnosed and inappropriately treated. They evaluated 4,376 individuals with headache through a computer-assisted telephone interview survey and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Socio-demographic data were expressed as mean±SD or percentages. The headache was considered as migraine in subjects who answered "Yes" to at least two out of the three questions of the Migraine ID-questionnaire 11,12,13,14 . Only data from subjects considered to have migraine were included in the present analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socio-demographic data were expressed as mean±SD or percentages. The headache was considered as migraine in subjects who answered "Yes" to at least two out of the three questions of the Migraine ID-questionnaire 11,12,13,14 . Only data from subjects considered to have migraine were included in the present analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The work activities were classified as employee ( full time or part-time) or self-employed. After this first step, the following questionnaires were applied with the app: ID migraine, in its validated Brazilian Portuguese version 11,12,13,14 , Brazilian Portuguese validated Headache Impact Test (HIT-6) 15,16 , and Brazilian Portuguese migraine/ headache WPAI 9 .…”
Section: Appmentioning
confidence: 99%
“…Various studies tried to simplify the diagnosis criteria of migraine to save time without compromising sensitivity and specificity. [32333435] Most of these studies tried to select few sensitive and specific clinical features for diagnosis of migraine. Prolonged duration of severe headache (4-72 hours), which limits physical or intellectual activity, photophobia and phonophobia, and nausea and/or vomiting were reported by most of these studies as useful questions to diagnose migraine.…”
Section: Discussionmentioning
confidence: 99%
“…This observation re enforces the statement that diagnosis of migraine should be considered in a person with recurrent headache for at least more than 3 months; of moderate-to-severe intensity; duration (4-72 hours); restricting physical/intellectual activity associated with nausea/vomiting, and photophobia/phonophobia. [32333435] Inappropriate diagnosis has its financial burden on patients. In our study, patients with delayed diagnosis paid more money from their pocket than those with early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The test has been validated in multiple contexts and has been used in previous migraine population-level studies because of its simplicity and accuracy compared to a clinical diagnosis. (12)(13)(14) A systematic review found that the pooled sensitivity of the test is 84% (95% con dence interval (CI): 75% − 90%) and speci city is 76% (95% CI: 69% − 83%). (12)…”
Section: Introductionmentioning
confidence: 99%